Advances in Forest Management under Global Change - Zhang, Ling (IntechOpen, 2020)
Advances in forest management will enhance the sustainable development of human society, and should be focused on. Under the context of global change, soil nutrients, especially nitrogen, should be carefully managed and monitored in plantations experiencing intensive nitrogen input, and forests with exotic plant invasion disturbance, considering its substantial contribution to global nitrous oxide. One negative effect of global change could be loss of biodiversity, which could be maintained by forest management. In addition, advanced technologies should also be developed to prevent fire in forests considering its increased frequency. Importantly, policies and technologies should also be developed for advanced forest management, such as deep learning in plant disease prevention, and quantitative strategic planning matrix in management of forest conservation.